The world on Mercators projection. - Arrowsmith, John, 1790-1873 (J. Arrowsmith, 1835)
Map shows parts of the voyages of exploration undertaken by Captain Cook, Captain Weddell and Captain Parry. Inset: Lands contiguous to the South Pole drawn to the equatorial scale of the map. Inset: Lands contiguous to the North Pole drawn to the equatorial scale of the map. Relief shown by hachures. Scale [ca. 1:35,000,000].